Odpowiedzi

2010-02-19T19:46:43+01:00
A) 7x²-4x-6x²+4-x²+5x=x+4
b) -2(3a-2b)-4a(2-3a+2b)=(-6a)+4b+8a-8ab=2a+4b-8ab
c)(4-x)(2x+5)-4=8x+20-2x²-5x=3x+20-2x²
d) (4-2x)(3x-3)-2x(3x+1)= 12x-12-6x²+6x-6x²-2x=16x-12-12x²
2010-02-19T19:49:10+01:00
A)=4+x
b)=-6a+4b-8a+12a do 2 -8 ab=-14a+12a do 2 +4b-8ab
c)=8x+20-2x do 2-5x-4=3x+16-2x do 2
d)=12x-12-6x do 2 +6x-6x do 2 -2x=-12+16x-12x do 2
  • Użytkownik Zadane
2010-02-19T19:49:38+01:00
A) 7x² -4x-6x² +4-x² +5x=x+4
b) -2(3a-2b)-4a(2-3a+2b)=-12a+4b+12a²-8ab
c) (4-x)(2x+5)-4=8x-2x²-5x+20=-2x²+3x+20
d) (4-2x)(3x-3)-2x(3x+1)= 12x-12-6x²+6x-6x²-2x=-12x²+16x-12